Predictors of school bullying perpetration in adolescence: A systematic review. (July 2015) - Álvarez-García, David; García, Trinidad; Núñez, José Carlos
Abstract: Bullying has negative effects on the victim, the aggressor and the bystanders. It is essential to determine the risk factors that can predict its onset in order to facilitate early identification of students at risk of becoming future victims or bullies and to optimize the design of measures for the prevention or treatment of bullying. Any measure in this regard should be based on the most solid scientific evidence available to date. The present work aims to undertake a systematic review of the scientific empirical articles published in the last decade that have analyzed possible risk factors predicting the perpetration of traditional school bullying in adolescence. From a search in the publications databases PsycInfo, Eric, and Web of Science, 85 articles that met the search requirements were selected. As a result of the analysis of the selected items, we identified the individual, school, family and community factors that increase the risk of bullying perpetration in adolescence, according to the available empirical evidence. We underscore the main points of agreement in the research community and the controversial aspects that still deserve to be studied in more depth. Highlights: Risk factors for school bullying perpetration in adolescence are examined. Individual, familiar, school and community predictors for being a bully are shown. Agreements and inconsistencies in this area of research are highlighted.